Woody carbon stock estimation in homegarden agroforestry along altitudinal gradients in southwest Ethiopia - Jegora, Tefera; Hundera, Kitessa; Kebebew, Zerihun; Bekele, Adugna Eneyew (Frontiers in Forests and Global Change, 2025)
Woody plant species in homegarden agroforestry store a large proportion of carbon stocks. However, there is limited information on the carbon stock potential of homegarden agroforestry along altitudinal gradients in southwest Ethiopia. Therefore, this study aims to estimate aboveground and belowground carbon stocks in homegardens using a non-destructive allometric model. Data were collected from 72 homegardens selected using a random sampling method. Woody plants were measured for diameter at breast height (DBH) of ≥ 5 cm and height of ≥ 1.5 m. The study revealed that the mean aboveground carbon stock (14.39 ± 2.95 Mg C ha−1) was significantly (p < 0.05) higher in the middle altitude than (6.12 ± 0.72 Mg C ha−1) in the low altitude. Carbon stocks were significantly different between middle and low altitudes. The overall mean carbon stock was 11.25 ± 1.60, with mean aboveground and belowground carbon stocks of 9.39 ± 1.34 and 1.88 ± 0.27 Mg C ha−1, respectively. The top 10 woody species contributed to 78.50% of the total carbon stock, of which 56.73% were Persea americana and Cordia africana. Wealth status and size of homegardens were significantly correlated (r = 0.298 and r = 0.307, respectively) with the carbon stock. The overall woody carbon stock distributions varied primarily due to altitudinal gradients, woody species, and socioeconomic factors. As a result, this study will assist researchers and policymakers in selecting optimal ecological areas and addressing socioeconomic gaps for agroforestry practices that produce biomass and store carbon for long-term climate change mitigation.